Necessidades formativas de professores do ensino superior, com vistas ao desenvolvimento profissional: o caso de uma universidade pública na Bahia - Ramos, Renata Adrian Ribeiro Santos (2013)
This research aimed to learn about the representations of teachers and managers in the UFRB (University of Reconcavo of Bahia) on formative needs in educational field,as part of professional development. For analytical understanding of the object of study, I used the theoretical foundations and methodological Theory of Social Representations (TRS), in the perspective of Jodelet (2001) and Abric (1999). Furthermore, contributions from authors of the field of teacher education and higher education pedagogy, such as: Zabalza (1998), Ibérnon (2010), Cunha (1999), Masetto (1998), served as a theoretical basis. From a methodological point of view: I made a Case Study, being that the research approach is qualitative and quantitative I used the questionnaire and the semi-structured interviews for data collection. Scientific research has allowed us to know that teachers have training needs in the pedagogical field and in respect to their own professional development. The managers of the institution believe that the teacher of the institution has formative needs, in pedagogical field. The institution develops a work for continuing education of teachers, approaching a philosophy of work based on reflection of educational practice. This dissertation is structured into five chapters, namely: 1)Delineation of the object of study, 2) conceptual aspects of teaching in higher education, 3)Social Representations, 4)Methodological Way, 5)Data Analysis. Finally realize a synthesis of the study in the final considerations, conceiving this research as a look at the formation of the teacher in higher education